Especificidad de la reacción de hemaglutinación en la artritis reumatoidea - Hernando Rocha Posada; Jaime Saravia Gómez; Miguel Guzmán Urrego (Revista de la Facultad de Medicina, 1961)
Hemagglutination reaction tess were made on 585 human serum obtained from patients with rheumatoid arthritis, patients with nom-rheumatoid arthritis joint diseases; patients with various medico-surgical diseases and normal subjects. Human erythrocytes, group O, Rh negative were sensitized with homologous serum. The results obtained gave a high specifity in the reaction of the cases with rheumatoid arthritis. Since the technique required for this test is simple, it is a very useful diagnostic aid in clinical practice.